Pharmacological Effects of Peganum Harmala L. Root Extract on Isolated Rat small Intestine - A, Shatarat; S, Abuhamdah; M, Al-Essa; F, Mohammed; S, Al-Olimat (Pharmacognosy Communications)
Background: Peganum harmala L. is a medicinal plant used in Jordan and in many countries in traditional medicine against several diseases, including gastrointestinal disorders. Objective: In this study, the effects of crude ethanolic root extract of P. harmala on the isolated smooth muscle of the rat jejunum intestine were investigated. Materials and Methods: The isolated organ bath method was adopted. The efficacy was recorded and analyzed by biological signal collection and analysis recording. Results: The ethanolic root extract inhibited the spontaneous contraction of rat jejunum and showed dose dependent inhibition of acetylcholine Ach (10–5 m) and potassium chloride KCl (60 mm), as well as inducing contractions of isolated rat jejunum. The extract also reduced barium chloride BaCl2 (5 mm) induced contractions of isolated rat jejunum dose-dependently. The inhibitions were statistically significant. Conclusion: These results indicated that the root extract of P. harmala possesses antispasmodic activity and justifies its use traditionally in alleviating gastrointestinal disorders.
Keywords: Gastrointestinal; Antispasmodic; Spasmolytic; Zygophyllaceace; Peganum harmala L.; Small intestine; Rats